Perovskite cell and preparation method thereof, laminated cell and photovoltaic cell assembly

By introducing an interface layer containing sulfinate groups and hydroxyl groups between the hole transport layer and the perovskite layer of the perovskite battery, the problem of gaps in the perovskite battery interface is solved, and the photoelectric conversion efficiency and interface durability of the battery are improved.

CN119855360APending Publication Date: 2025-04-18BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411581804.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-04-18

Smart Images

  • Figure CN119855360A_ABST
    Figure CN119855360A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite cell and a preparation method thereof, a laminated cell and a photovoltaic cell assembly, the perovskite cell comprises a first charge transport layer, an interface layer, a perovskite layer and a second charge transport layer which are laminated in sequence, the material of the interface layer contains sulfinic acid groups, and the material of the first charge transport layer contains hydroxyl groups. According to the perovskite cell, the connection strength of the hole transport layer and the perovskite layer can be improved, the perovskite layer is more compact, non-radiative recombination of electrons and holes can be effectively inhibited, extraction and transport of carriers are enhanced, and therefore the photoelectric conversion efficiency of the cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite cells, and in particular to a perovskite cell and a preparation method thereof, a laminated cell, and a photovoltaic cell assembly. Background Art

[0002] In the context of carbon neutrality and carbon peak, photovoltaics is an indispensable technology for building a safe, clean, low-carbon and efficient energy system. Perovskite has the advantages of low preparation cost, high absorption coefficient and low exciton binding energy, making perovskite solar cells (PSCs) gradually become an important development direction in the photovoltaic field.

[0003] The buried interface of perovskite cells, especially the interface between the electron transport layer or the hole transport layer and the perovskite layer, is a key area for charge transfer and recombination. The quality of this interface directly affects the photogenerated carrier extraction efficiency, recombination rate and overall photoelectric performance of the cell. However, if the existing perovskite layer is directly deposited on the surface of the electron transport layer or the hole transport layer, there will still be gaps of tens to hundreds of nanometers at the bottom of the perovskite film. These gaps will not only lead to charge accumulation, but also trigger various decomposition processes of the perovskite after recombination, which is one of the main reasons for the deterioration of the buried interface and the reduction of interface durability. Summary of the invention

[0004] The present invention provides a perovskite battery. The perovskite battery can not only improve the connection strength between the hole transport layer and the perovskite layer and make the perovskite layer more compact by introducing an interface layer between the hole transport layer and the perovskite layer, but also passivate the defects at the bottom of the perovskite layer and the surface of the hole transport layer, effectively inhibit the non-radiative recombination of electrons and holes, enhance the extraction and transport of carriers, and thus significantly improve the photoelectric conversion efficiency of the battery.

[0005] The present invention also provides a method for preparing a perovskite battery. The method is simple to operate and can successfully prepare the above-mentioned perovskite battery.

[0006] The present invention also provides a stacked cell comprising the above-mentioned perovskite cell, and the stacked cell has good working stability and high photoelectric conversion efficiency.

[0007] The present invention also provides a photovoltaic cell assembly comprising the above-mentioned perovskite cell or stacked cell, and the photovoltaic cell assembly has the advantages of high photoelectric conversion efficiency and long service life.

[0008] In detail, in a first aspect, the present invention provides a perovskite battery comprising a first charge transport layer, an interface layer, a perovskite layer, and a second charge transport layer stacked in sequence, wherein the material of the interface layer contains a sulfinic acid group, and the material of the first charge transport layer contains a hydroxyl group.

[0009] Furthermore, the molar ratio of the sulfinic acid group to the hydroxyl group is 1-2:1-2.

[0010] Furthermore, the material of the interface layer also includes formamidinium groups; and the crystal structure of the perovskite layer includes formamidinium ions.

[0011] Furthermore, the material of the interface layer includes a compound having a structure as shown in Formula 1 and / or Formula 2:

[0012] Formula 1, Formula 2;

[0013] In Formula 2, X is H or a metal ion; R is a C1-C10 saturated alkyl group, a C1-C10 unsaturated alkyl group, a C1-C10 saturated alkyl group containing a C1-C10 alkyl branch, a C1-C10 unsaturated alkyl group containing a C1-C10 alkyl branch, a benzene ring, or a benzene ring containing a substituent.

[0014] Further, when the first charge transport layer is a hole transport layer, the material of the hole transport layer is a self-assembled molecule;

[0015] And / or, when the first charge transport layer is an electron transport layer, the material of the electron transport layer is at least one of a hydrogen-bonded metal oxide, a hydrogen-bonded metal sulfide, a hydrogen-bonded fullerene and its derivatives, and a hydrogen-bonded conjugated polymer.

[0016] Furthermore, the thickness of the interface layer is 10-30 nm.

[0017] Furthermore, the perovskite cell further includes a transparent conductive substrate, and the transparent conductive substrate is located on a surface of the first charge transport layer away from the interface layer.

[0018] Furthermore, the perovskite cell comprises: a transparent conductive substrate, a hole transport layer, the interface layer, a perovskite layer, an electron transport layer and an electrode stacked in sequence.

[0019] Furthermore, the average grain size of the perovskite layer is 950nm-2000nm.

[0020] Furthermore, a hole blocking layer is provided on the surface of the second electron transport layer.

[0021] In a second aspect, the present invention provides a method for preparing the above-mentioned perovskite battery, comprising the following steps:

[0022] Preparing a first charge transport layer on the surface of the substrate;

[0023] The interface layer material is dispersed in a solvent, the obtained dispersion is spin-coated on the surface of the first charge transport layer, and the interface layer is obtained after a single annealing;

[0024] The perovskite solution is spin-coated on the surface of the interface layer, and after secondary annealing, a perovskite layer is obtained;

[0025] A second charge transport layer is prepared on the surface of the perovskite layer.

[0026] Furthermore, the first charge transport layer is prepared by the following process:

[0027] The liquid including the first charge transport material is spin-coated on the surface of the substrate at a speed of 2000-6000 rpm, and after drying, the first charge transport layer is obtained.

[0028] Furthermore, in the dispersion, the concentration of the interface layer material is 0.1-0.5 mg / mL, and / or the spin coating speed of the dispersion is 3000-6000 rpm, and / or the primary annealing temperature is 80-120°C.

[0029] Furthermore, the spin coating speed of the perovskite solution is 1000-3000 rpm, and / or the temperature of the secondary annealing is 100-170°C.

[0030] Furthermore, the second charge transport layer is prepared by the following process:

[0031] The second charge transport material is evaporated on the surface of the interface layer at a rate of 0.01-0.02nm / s at 400-600°C to obtain the second charge transport layer; or a solution including the second charge transport material is spin-coated on the surface of the perovskite layer at a speed of 2000-5000rpm, and after drying, the second charge transport layer is obtained.

[0032] In a third aspect, the present invention provides a stacked battery comprising the perovskite battery described in the first aspect.

[0033] In a fourth aspect, the present invention provides a photovoltaic cell assembly comprising the perovskite cell described in the first aspect or the stacked cell described in the third aspect.

[0034] The perovskite battery provided by the present invention can not only improve the connection strength between the first charge transport layer and the perovskite layer and make the perovskite layer more compact by introducing an interface layer between the first charge transport layer and the perovskite layer, but also passivate the defects of the perovskite layer, effectively inhibit the non-radiative recombination of electrons and holes, enhance the extraction and transport of carriers, and thus improve the photoelectric conversion efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0036] Figure 1 It is a comparison diagram of the current density and voltage (JV) characteristic curves of the perovskite cells of Example 1, Comparative Example 1 and Comparative Example 2;

[0037] Figure 2 It is the electrochemical impedance spectrum fitting diagram of the perovskite battery of Example 1, Comparative Example 1 and Comparative Example 2;

[0038] Figure 3 Surface SEM images of the perovskite layers of the perovskite cells of Example 1, Comparative Example 1 and Comparative Example 2;

[0039] Figure 4 This is a SEM image of the buried bottom surface of the perovskite layer peeled off from the perovskite cells of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] In this application, references to "one embodiment", "an example", or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment, embodiment, or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment", "an embodiment", "an example", or "an example" appearing in various places throughout the specification do not necessarily refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any appropriate combination and / or sub-combination.

[0042] In a first aspect, the present invention provides a perovskite battery comprising a first charge transport layer, an interface layer, a perovskite layer, and a second charge transport layer stacked in sequence, wherein the material of the interface layer contains a sulfinic acid group, and the material of the first charge transport layer contains a hydroxyl group.

[0043] In the present invention, by introducing an interface layer between the first charge transport layer and the perovskite layer, not only can the connection strength between the first charge transport layer and the perovskite layer be improved, making the perovskite film more compact, but also the defects at the bottom of the perovskite layer and the surface of the first charge transport layer can be passivated, effectively suppressing the non-radiative recombination of electrons and holes, enhancing the extraction and transport of carriers, and thus improving the photoelectric conversion efficiency of the battery. In detail, the material of the interface layer contains sulfinic acid groups, which can be anchored on the surface through a quasi-esterification reaction with the hydroxyl group of the first charge transport layer (quasi-esterification reaction: CH 3 N 2 SO 2 H+R-OH=CH 3 N 2 SOOR), so the interface layer can establish a tight, durable and reinforced buried interface between the first charge transport layer and the perovskite layer, strongly connect the first charge transport layer to the perovskite layer, and passivate the defects at the bottom of the perovskite and the surface of the first charge transport layer, effectively inhibit non-radiative recombination, enhance the extraction and transport of carriers, and thus reduce the voltage loss.

[0044] In some embodiments, the molar ratio of the sulfinic acid group to the hydroxyl group is 1-2:1-2.

[0045] Among them, the sulfinic acid group and the hydroxyl group in the molar ratio as mentioned above can fully react, so that the interface layer is more stably anchored on the surface of the first charge transport layer, thereby establishing a closer interface between the first charge transport layer and the perovskite layer, passivating the defects at the bottom of the perovskite and the surface of the first charge transport layer, effectively inhibiting non-radiative recombination, and enhancing the extraction and transport of carriers.

[0046] In some embodiments, the PCE of the perovskite cell with an interface layer is 24.85%, which is better than the reference value of 20.56% for the perovskite cell without an interface layer.

[0047] In a specific embodiment, the material of the interface layer further includes formamidinium groups; and the crystal structure of the perovskite layer includes formamidinium ions.

[0048] The material of the interface layer as described above contains formamidinium groups and sulfinic acid groups, which interact with the perovskite and hole transport layer respectively. On the one hand, the sulfinic acid group is anchored on the surface through an esterification reaction with the hydroxyl group of the hole transport layer; on the other hand, the formamidinium group can fill the vacancy of the formamidinium cation in the perovskite layer and occupy the lattice site of the perovskite, as a part of the perovskite, thereby synergistically improving the connection strength between the first charge transport layer and the perovskite layer, making the perovskite film denser, and further passivating the defects at the bottom of the perovskite layer and the surface of the first charge transport layer, effectively inhibiting the non-radiative recombination of electrons and holes.

[0049] In a specific embodiment, the material of the interface layer includes a compound with a structure as shown in Formula 1 and / or Formula 2:

[0050] Formula 1, Formula 2;

[0051] In Formula 2, X is H or a metal ion; R is a C1-C10 saturated alkyl group, a C1-C10 unsaturated alkyl group, a C1-C10 saturated alkyl group containing a C1-C10 alkyl branch, a C1-C10 unsaturated alkyl group containing a C1-C10 alkyl branch, a benzene ring, or a benzene ring containing a substituent.

[0052] In a specific embodiment, R is a C1-C5 saturated alkyl group or a C1-C5 saturated alkyl group containing a C1-C3 alkyl branch.

[0053] In another specific embodiment, the material of the interface layer is any one or more of sodium p-toluenesulfinate, sodium dithionite, sodium benzenesulfinate, and sodium formaldehyde sulfoxylate.

[0054] In some embodiments of the present invention, the chemical composition of the perovskite material can be adjusted to optimize it so that it better matches the energy level between the interface layer and the perovskite layer, which helps to further reduce the energy loss at the interface and improve the carrier transport efficiency.

[0055] In a specific embodiment, the material of the perovskite layer is ABX 3 A compound of the type, wherein X is a halogen anion, and X is selected from I - Br - and Cl - One or a combination of any of the ions in the formula (A) or (B), wherein A and B are cations of different sizes, the cation at position A is a monovalent cation, which may be an organic-inorganic ion hybrid or an inorganic cation, and specifically, A is selected from FA + , and FA + Other than MA + , Cs + , Rb + and K + One or a combination of any of the ions in the formula (A), B is a divalent cation selected from Pb 2+ 、Eu 2+ Sn 2+ and Cs + One or a combination of any of the ions in the ion array.

[0056] In one embodiment, the crystal structure of the perovskite layer is CsFAPbI 3 , CsFAPbI 3Compared with other components, perovskite performs better in photoelectric conversion efficiency and has better device stability.

[0057] When the first charge transport layer is a hole transport layer, the material of the hole transport layer is a self-assembled molecule;

[0058] And / or, when the first charge transport layer is an electron transport layer, the material of the electron transport layer is at least one of a hydrogen-bonded metal oxide, a hydrogen-bonded metal sulfide, a hydrogen-bonded fullerene and its derivatives, and a hydrogen-bonded conjugated polymer.

[0059] In some embodiments, the self-assembling molecules include [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid or a mixture of the two, wherein the hole transport layer of this structure can improve the wettability of thin film deposition on the basis of reducing clusters.

[0060] In some embodiments, the material of the electron transport layer is C 60 or [6,6]-phenyl-C 61 -Methyl butyrate.

[0061] In a specific embodiment, the thickness of the interface layer is 5-30 nm, wherein if the thickness of the interface layer is too thin, the interface adhesion strength may be weakened, and if the thickness of the interface layer is too thick, its light transmittance may be affected.

[0062] It can be understood that in the present invention, the perovskite cell can be a trans (pin) structure or a regular (nip) structure.

[0063] When the perovskite cell is a trans (pin) structure, in a specific embodiment, the perovskite cell includes: a transparent conductive substrate, a hole transport layer, the interface layer, a perovskite layer, an electron transport layer and an electrode stacked in sequence.

[0064] When the perovskite cell is a formal (nip) structure, in a specific embodiment, the perovskite cell includes: a transparent conductive substrate, an electron transport layer, the interface layer, a perovskite layer, a hole transport layer and an electrode stacked in sequence.

[0065] When the perovskite cell is of a trans (pin) structure, in a specific embodiment, the perovskite cell further comprises a transparent conductive substrate, and the transparent conductive substrate is located on a surface of the first charge transport layer away from the interface layer.

[0066] In a specific embodiment, the average grain size of the perovskite layer is 950nm-2000nm. The grains in the above-mentioned grain size range have fewer grain boundaries, and the grain boundaries are the centers of charge carrier recombination. Therefore, the perovskite layer as described above can reduce the recombination loss, thereby further improving the photoelectric conversion efficiency of the battery.

[0067] In some embodiments, the average grain size of the perovskite layer is 1000-2000 nm.

[0068] In a specific embodiment, a hole blocking layer is provided on the surface of the second electron transport layer, wherein the hole blocking layer can reduce surface defects and interface states, thereby avoiding carrier recombination and reducing device efficiency.

[0069] In a specific embodiment, the material of the hole blocking layer is 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, also known as bathocuproine (BCP), whose energy band can guide electrons to pass through, but holes cannot pass through. Therefore, a hole blocking layer is formed on the surface of the electron transport layer to block holes from diffusing to the electrode and prevent metal ions in the electrode from damaging the transport layer.

[0070] In some embodiments of the present invention, the electrode is selected from one of a transparent conductive oxide, a silver electrode, a copper electrode, a gold electrode and a carbon electrode.

[0071] In some embodiments of the present invention, the thickness of the electrode is 50nm-150nm. Although the greater the thickness of the electrode layer, the smaller its resistance value and the higher the photoelectric conversion efficiency of the battery, the thickness of the electrode layer still needs to be controlled within a more appropriate range to avoid serious hysteresis of the battery; in addition, it can also avoid the phenomenon that the near-infrared light transmittance is weakened due to the excessive thickness of the transparent electrode layer, which affects the battery performance. Exemplarily, the thickness of the electrode is 50, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, etc.

[0072] In some embodiments of the present invention, the thickness of the hole transport layer is in the range of 5nm-30nm. The hole transport layer has a suitable thickness to completely cover the conductive substrate and ensure the smooth collection of carriers, avoiding the phenomenon of excessive absorption of photons leading to a decrease in the short-circuit current density of the battery. Exemplarily, the thickness of the hole transport layer can be 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, etc.

[0073] The perovskite layer is the core part of the perovskite solar cell, responsible for absorbing light and generating photogenerated carriers (electrons and holes). The choice of its thickness has a significant impact on the photoelectric conversion efficiency, charge transfer performance and stability of the battery. Technicians can prepare a perovskite layer of appropriate thickness according to different materials and preparation processes. In some embodiments of the present invention, the thickness of the perovskite layer is 400nm-1000nm. Within this range, as the thickness of the perovskite layer increases, the battery can absorb more photons and generate more photogenerated carriers, thereby improving the photoelectric conversion efficiency. However, after the thickness increases to 600nm, the growth rate of the photoelectric conversion efficiency will slow down or even decrease. Exemplarily, the thickness of the perovskite layer can be 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, etc.

[0074] In some embodiments of the present invention, the thickness of the electron transport layer is 20nm-60nm. Among them, the thickness of the electron transport layer is controlled within the above range, and the photoelectric conversion efficiency of the perovskite solar cell is relatively high. This is because within this thickness range, the electron transport layer can not only effectively collect and transmit electrons, but also maintain a good light absorption capacity; if the thickness of the electron transport layer is too small, it may cause the electron tunneling effect to be enhanced, and the electrons are easily deactivated during the transmission process, thereby reducing the photoelectric conversion efficiency. If the thickness of the electron transport layer is too large, although the transmission capacity of electrons can be enhanced, the light absorption capacity will be weakened accordingly, which will also reduce the photoelectric conversion efficiency. Exemplarily, the thickness of the electron transport layer can be 20nm, 22nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 58nm, 60nm, etc.

[0075] In a second aspect, the present invention provides a method for preparing the above-mentioned perovskite battery, comprising the following steps:

[0076] Preparing a first charge transport layer on the surface of the substrate;

[0077] The interface layer material is dispersed in a solvent, the obtained dispersion is spin-coated on the surface of the first charge transport layer, and the interface layer is obtained after a single annealing;

[0078] The perovskite solution is spin-coated on the surface of the interface layer, and after secondary annealing, a perovskite layer is obtained;

[0079] A second charge transport layer is prepared on the surface of the perovskite layer.

[0080] In some embodiments of the present invention, the first charge transport layer is prepared by the following process:

[0081] The liquid including the first charge transport material is spin-coated on the surface of the substrate at a speed of 2000-64000 rpm, and after drying, the first charge transport layer is obtained.

[0082] Among them, the above-mentioned embodiment can assist in forming a more uniform first charge transport layer by controlling the spin coating speed of the liquid including the first charge transport material, so as to reduce defects and uneven areas, thereby avoiding affecting the charge transport efficiency of the first charge transport layer.

[0083] In some embodiments of the present invention, the concentration of the interface layer material in the dispersion is 0.1-0.5 mg / mL, and / or the spin coating speed of the dispersion is 3000-6000 rpm, and / or the primary annealing temperature is 80-120°C.

[0084] Among them, the above-mentioned embodiment can optimize the conductivity and energy level matching of the interface layer by controlling the concentration of the interface layer material, thereby improving the charge transfer efficiency. Furthermore, the spin coating speed of the dispersion within the above-mentioned range can reduce the defects and uneven areas of the interface layer. Furthermore, a single annealing within the above-mentioned temperature range helps to remove the solvent residue in the interface layer and ensure the complete volatilization of the solvent, thereby reducing impurities and defects in the interface layer.

[0085] In some embodiments of the present invention, the spin coating speed of the perovskite solution is 1000-3000 rpm, and / or the temperature of the secondary annealing is 100-170°C.

[0086] The spin coating speed as described above can promote better crystallization of perovskite, reduce grain boundary defects in the perovskite layer, and thus improve its charge transfer efficiency; while the annealing at the temperature as described above helps to remove the residual solvent in the perovskite layer, ensuring complete volatilization of the solvent, thereby further reducing impurities and defects in the perovskite layer.

[0087] In some embodiments of the present invention, the second charge transport layer is prepared by the following process:

[0088] The second charge transport material is evaporated on the surface of the interface layer at a rate of 0.01-0.02nm / s at 500-600°C to obtain the second charge transport layer; or a solution including the second charge transport material is spin-coated on the surface of the perovskite layer at a speed of 2000-5000rpm, and after drying, the second charge transport layer is obtained.

[0089] Among them, the above-mentioned embodiment can promote the second charge transport layer to form good crystallization and a smooth surface by controlling the evaporation temperature and rate, thereby improving its charge transfer efficiency, or, by controlling the spin coating speed of the liquid of the second charge transport material, it can assist in forming a more uniform second charge transport layer to reduce defects and uneven areas, thereby improving the charge transfer efficiency of the second charge transport layer.

[0090] In a third aspect, the present invention provides a stacked battery comprising the perovskite battery described in the first aspect.

[0091] In a fourth aspect, the present invention provides a photovoltaic cell assembly comprising the perovskite cell described in the first aspect or the stacked cell described in the third aspect.

[0092] The technical scheme of the present invention is further illustrated below in conjunction with specific examples. All parts, percentages and ratios described in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.

[0093] Example 1

[0094] This example provides a perovskite cell, comprising a conductive glass, a hole transport layer, an interface layer, a perovskite layer, an electron transport layer, a BCP and an electrode stacked in sequence;

[0095] The materials and components of each layer of the perovskite cell are as follows: ① Conductive glass: FTO, thickness 2.2 mm; ② Hole transport layer: MeO-2PACz / Me-4PACz, thickness 15 nm; ③ Interface layer: thiourea dioxide (FASA), thickness 10 nm; ④ Perovskite layer: CsFAPbI 3 , thickness is 650nm; ⑤Electron transport layer: C 60 , thickness is 35nm; ⑥ hole blocking layer: BCP, thickness is 6nm; ⑦ electrode: Ag, thickness is 100nm; wherein the molar ratio of the sulfinic acid group in thiourea dioxide to the hydroxyl group in the hole transport layer is 1.6:1.

[0096] Its production process is:

[0097] ① Use Tac-Tac-Clean to clean the conductive surface of the conductive glass, put it in a beaker, use deionized water containing detergent to cover the glass, wrap the beaker with aluminum foil to prevent dust from falling in, ultrasonicate for 10 minutes, pour out the detergent, add deionized water to clean, pour it out after the end, add deionized water and continue ultrasonicating for 10 minutes, finally pour out the water and add anhydrous ethanol to ultrasonicate for 10 minutes. Take it out with tweezers, blow dry with a nitrogen air gun, and put it in a drying oven.

[0098] ② Take out the clean conductive glass, place it in a culture dish with the conductive surface facing up, and then perform plasma surface treatment (pass high-purity oxygen, power 120 W, treatment for 8 min). Use a pipette to take the solution of the hole transport layer material and spread it on the substrate surface. Use a coater to spin coat it on the conductive glass at 3000 rpm for 30 seconds, and then dry it on a heating table at 100°C for 10 minutes to obtain the conductive glass and hole transport layer stacked in sequence.

[0099] ③ Accurately weigh FASA using an electronic balance, dissolve it in ethanol, prepare a FASA solution with a concentration of 0.3 mg / mL, spin-coat it on the surface of the hole transport layer at 4000 rpm, anneal at 100 °C for 10 min, and after cooling, transfer it to a nitrogen glove box for use in the sequentially stacked conductive glass, hole transport layer, and interface layer.

[0100] ④ Use an analytical balance to weigh appropriate amounts of cesium chloride (CsCl) and lead iodide (PbI 2 ) was dissolved in a mixed solvent of DMF (N,N-dimethylformamide) and DMSO (dimethyl sulfoxide), and an inorganic lead halide solution was prepared after complete dissolution. The lead iodide solution was drawn with a pipette and dropped onto the upper surface. After spin coating at 1700 rpm for 30 seconds, it was placed on a 70°C heating table and dried for 1 minute. After cooling to room temperature, a semi-wet yellow transparent film was presented, forming an inorganic lead halide layer. FAI (formamidine hydroiodide) and MACl (methylamine chloride) were dissolved in isopropyl alcohol (IPA) to prepare an ammonium salt solution, which was spin coated at 1800 rpm for 30 seconds, and annealed in a drying oven at 150°C for 15 minutes. After the perovskite annealing was completed, it was cooled to obtain a conductive glass, a hole transport layer, an interface layer, and a perovskite layer stacked in sequence.

[0101] ⑤ Open the cooling water circulation system of the evaporation equipment, turn on the gas, turn on the key switch, unscrew the chamber door, open the drain valve, wait for the air pressure to rise to atmospheric pressure, open the chamber door, use the analytical balance to weigh about 40mg of C60 powder, place it in the evaporation crucible, put the sample on the mask, and fix it to the substrate plate. Close the chamber door, close the baffle, switch to the vacuum interface, select the automatic mode, press and hold the automatic start for about 3 seconds, turn on the ionization, wait for a total of about 55 minutes, and the ionization gauge reaches 10 -4 Pa, turn on the heating, adjust the temperature to about 550°C, open the baffle after reaching the specified temperature and start evaporation, maintain the rate at 0.1-0.2A / s, close the baffle when the film thickness reaches 30nm, start exhaust when the temperature drops to 300°C, take out the sample and put it into a nitrogen glove box to obtain conductive glass, hole transport layer, interface layer, perovskite layer and electron transport layer stacked in sequence.

[0102] ⑥ Prepare 0.5 mg / mL BCP, the solvent is IPA, take 70 μL with a pipette and spin coat at 5000 rpm for 30 seconds, dry at 70°C for 3-5 minutes, and the BCP preparation is completed to obtain the conductive glass, hole transport layer, interface layer, perovskite layer, electron transport layer, and BCP hole blocking layer stacked in sequence.

[0103] ⑦ Use tweezers to hold 1-2 silver particles and place them on the evaporation boat. After reaching the specified pressure, increase the evaporation source power. After the rate stabilizes at 1A / s, open the baffle and start evaporation. The electrode thickness is 100nm, and a perovskite battery is obtained.

[0104] Example 2

[0105] The difference from Example 1 is that the thickness of the interface layer is 16 nm. The specific preparation process refers to Example 1, except that step ③ is changed to prepare a FASA solution with a concentration of 0.4 mg / mL; wherein the molar ratio of the sulfinic acid group in thiourea dioxide to the hydroxyl group in the hole transport layer is 2:1.

[0106] Example 3

[0107] The difference from Example 1 is that the thickness of the interface layer is 24 nm. The specific preparation process refers to Example 1, except that step ③ is changed to prepare a FASA solution with a concentration of 0.5 mg / mL; wherein the molar ratio of the sulfinic acid group in thiourea dioxide to the hydroxyl group in the hole transport layer is 2.6:1.

[0108] Example 4

[0109] The difference from Example 1 is that the material of the interface layer is sodium p-toluenesulfinate.

[0110] The specific preparation process refers to Example 1, except that: step 3 is changed to accurately weigh sodium p-toluenesulfinate with an electronic balance and dissolve it in ethanol to prepare a solution concentration of 0.3 mg / mL; wherein the molar ratio of the sulfinic acid group in thiourea dioxide to the hydroxyl group in the hole transport layer is 1.2:1, spin-coated on the hole transport surface at 4000 rpm, annealed at 100°C for 10 min, and after cooling, transferred to a nitrogen glove box for standby use. The conductive glass, hole transport layer, and interface layer are stacked in sequence.

[0111] Example 5

[0112] The difference from Example 1 is that the material of the interface layer is sodium dithionite.

[0113] The specific preparation process refers to Example 1, except that: step 3 is changed to accurately weigh sodium dithionite with an electronic balance and dissolve it in ethanol to prepare a solution concentration of 0.3 mg / mL; wherein the molar ratio of the sulfinic acid group in thiourea dioxide to the hydroxyl group in the hole transport layer is 1.2:1, spin-coated on the hole transport surface at 4000 rpm, annealed at 100°C for 10 min, and after cooling, transferred to a nitrogen glove box for standby use. The conductive glass, hole transport layer, and interface layer are stacked in sequence.

[0114] Example 6

[0115] The difference from Example 1 is that the crystal structure of the perovskite layer does not include formamidinium ions, and its molecular formula is MAPbI 3 .

[0116] Comparative Example 1

[0117] The difference from Example 1 is that the perovskite cell does not contain an interface layer.

[0118] The specific preparation process refers to Example 1, except that step ③ is changed to ethanol rinsing, and the mixture is spin-coated on the hole transport layer at a rotation speed of 4000 rpm.

[0119] Comparative Example 2

[0120] The difference from Example 1 is that the perovskite cell does not contain an interface layer.

[0121] The specific preparation process refers to Example 1, except that step ④ is changed to doping 0.6 mol / L FASA in the ammonium salt solution to prepare the perovskite layer.

[0122] Comparative Example 3

[0123] The difference from Example 1 is that the perovskite cell contains an interface layer but the first charge transport layer does not contain hydroxyl groups.

[0124] The specific preparation process refers to Example 1, except that the hole transport material in step ② is changed to PTAA, i.e. poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine].

[0125] Test Case

[0126] JV Testing

[0127] The current density and voltage (JV) characteristic curves of the perovskite cells of the above embodiments and comparative examples were tested using a xenon lamp solar simulator (USHIO, UXL-300D-0, Japan), wherein the light power was calibrated to 100 mW·cm by a crystalline silicon reference cell. 2All devices were measured using a Keithley 2400 source meter in sweep mode with a reverse sweep (from 1.2 V to -0.1 V) and a forward sweep (from -0.1 V to 1.2 V) at a rate of 0.02 V·s -1 , delay time 0ms, and the light-transmitting surface can be wiped with a dust-free cloth before measurement. Some test results are shown in Table 1 and Figure 1 As shown:

[0128] surface :

[0129]

[0130] It can be seen from Table 1 that, compared with the comparative example, the embodiment has greatly improved the FF and Voc of the perovskite battery due to the addition of the interface layer before the perovskite deposition.

[0131] EIS Test

[0132] The perovskite cells of the above embodiments and comparative examples were used as samples to be tested, and the electrochemical workstation was started. A DC bias of 0.9V was applied to the samples, and an AC voltage with an amplitude of 10-20mV was used as a disturbance signal. The test frequency was 0.1-106Hz, and the original impedance spectrum data was obtained. The data was fitted using Zview, and an equivalent circuit model was established, and finally the component parameters of the model were obtained; some test results are shown in Table 2 and Figure 2 As shown:

[0133] Table 2:

[0134]

[0135] It can be seen from Table 2 that compared with the comparative example, the device composite resistance of the FASA interface layer (Rre=4040Ω) of the embodiment is larger. The larger the composite resistance, the smaller the energy loss caused by carrier recombination. Therefore, the perovskite battery of the embodiment has more efficient charge transport and absorption.

[0136] Scanning electron microscope test

[0137] First, use diagonal pliers to cut the perovskite samples of the above examples and comparative examples into 1 cm 2 The small pieces on the left and right are covered with conductive glue, placed in the sample rack and evacuated. Open the sample stage navigation interface, select the corresponding sample, control the height of the sample stage, and pressurize. Switch to the photo mode, select the appropriate EHT, probe, aperture and WD, adjust the focus, anastigmatism, contrast, and brightness to make the image clearer, and finally save the picture. Some test results are shown in Table 3 and Figure 3 As shown:

[0138] Table 3:

[0139]

[0140] It can be seen from Table 3 that compared with Comparative Example 1, after adding the interface layer in Example 1, the average grain size of the perovskite increases from 0.86 μm to 1.88 μm, and Figure 3 It can be seen that compared with Comparative Examples 1-2, the perovskite film of Example 1 appears to have fewer pores and is denser.

[0141] Interface strength test

[0142] The perovskite films of the perovskite cells of Example 1 and Comparative Example 1 were peeled off using UV curing adhesive, and then the peeled buried bottom films were tested using a scanning electron microscope. The results are shown in FIG. Figure 4 .

[0143] Depend on Figure 4 It can be seen that the bottom surface peeled off from the hole transport layer of Comparative Example 1 presents complete perovskite particles, while the bottom surface peeled off from the interface layer of Example 1 is observed to be broken large pieces of perovskite, unlike the sample of Comparative Example 1 which can be directly separated at the buried interface, indicating that the perovskite layer based on the interface layer has a stronger interface adhesion strength, and the perovskite battery containing the interface layer has a tighter and enhanced interface connection, which may even exceed the strength of the perovskite body.

[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A perovskite battery, characterized in that: The invention comprises a first charge transport layer, an interface layer, a perovskite layer and a second charge transport layer which are stacked in sequence. The material of the interface layer contains a sulfinic acid group, and the material of the first charge transport layer contains a hydroxyl group.

2. The perovskite battery according to claim 1, characterized in that: The molar ratio of the sulfinic acid group to the hydroxyl group is 1-2:1-2.

3. The perovskite battery according to claim 1 or 2, characterized in that: The material of the interface layer further includes formamidinium groups; and the crystal structure of the perovskite layer includes formamidinium ions.

4. The perovskite battery according to claim 1 or 2, characterized in that: The material of the interface layer includes a compound having a structure as shown in Formula 1 and / or Formula 2: Formula 1, Formula 2; In Formula 2, X is H or a metal ion; R is a C1-C10 saturated alkyl group, a C1-C10 unsaturated alkyl group, a C1-C10 saturated alkyl group containing a C1-C10 alkyl branch, a C1-C10 unsaturated alkyl group containing a C1-C10 alkyl branch, a benzene ring, or a benzene ring containing a substituent.

5. The perovskite battery according to any one of claims 1 to 4, characterized in that: When the first charge transport layer is a hole transport layer, the material of the hole transport layer is a self-assembled molecule; And / or, when the first charge transport layer is an electron transport layer, the material of the electron transport layer is at least one of a hydrogen-bonded metal oxide, a hydrogen-bonded metal sulfide, a hydrogen-bonded fullerene and its derivatives, and a hydrogen-bonded conjugated polymer.

6. The perovskite battery according to any one of claims 1 to 5, characterized in that: The thickness of the interface layer is 10-30 nm.

7. The perovskite battery according to any one of claims 1 to 6, characterized in that: The perovskite cell further includes a transparent conductive substrate, which is located on a surface of the first charge transport layer away from the interface layer.

8. The perovskite cell according to claim 7, characterized in that: The perovskite cell comprises: a transparent conductive substrate, a hole transport layer, the interface layer, a perovskite layer, an electron transport layer and an electrode stacked in sequence.

9. The perovskite battery according to claim 7, characterized in that: The average grain size of the perovskite layer is 950nm-2000nm.

10. The perovskite cell according to claims 1-6, characterized in that: A hole blocking layer is provided on the surface of the second electron transport layer.

11. A method for preparing a perovskite battery according to any one of claims 1 to 10, characterized in that: The following steps are involved: Preparing a first charge transport layer on the surface of the substrate; Dispersing the interface layer material in a solvent, spin-coating the obtained dispersion on the surface of the first charge transport layer, and annealing once to obtain the interface layer; The perovskite solution is spin-coated on the surface of the interface layer, and after secondary annealing, a perovskite layer is obtained; A second charge transport layer is prepared on the surface of the perovskite layer.

12. The preparation method according to claim 11, characterized in that: The first charge transport layer is specifically prepared by the following process: The liquid including the first charge transport material is spin-coated on the surface of the substrate at a speed of 2000-6000 rpm, and after drying, the first charge transport layer is obtained.

13. The preparation method according to claim 11, characterized in that: In the dispersion, the concentration of the interface layer material is 0.1-0.5 mg / mL, and / or the spin coating speed of the dispersion is 3000-6000 rpm, and / or the primary annealing temperature is 80-120°C.

14. The preparation method according to claim 11, characterized in that: The spin coating speed of the perovskite solution is 1000-3000 rpm, and / or the temperature of the secondary annealing is 100-150°C.

15. The preparation method according to claim 11, characterized in that: The second charge transport layer is specifically prepared by the following process: The second charge transport material is evaporated on the surface of the interface layer at a rate of 0.01-0.02nm / s at 500-600°C to obtain the second charge transport layer; or a solution including the second charge transport material is spin-coated on the surface of the perovskite layer at a speed of 2000-5000rpm, and after drying, the second charge transport layer is obtained.

16. A laminated battery, characterized in that: A perovskite battery comprising any one of claims 1-10.

17. A photovoltaic cell assembly, characterized in that: The photovoltaic cell assembly comprises the perovskite cell according to any one of claims 1 to 10 or the stacked cell according to claim 16.